PENINGKATAN LITERASI TENTANG TEKNOLOGI KEUANGAN (FINANCIAL TECHNOLOGY) PADA SANTRI AL-ASHRIYYAH NURUL IMAN ISLAMIC BOARDING SCHOOL BOGOR, JAWA BARAT - Purwana, Dedi; Effendi, Mohammad Sofwan; Widyastuti, Umi; Wibowo, Setyo Ferry; Suparno, Suparno; Wibowo, Agus; Cedaryana, Cedaryana; Lenggogeni, Lenggogeni; Lestari, Friska Aviyanti; Ghifari, Ezar Atira Anamta (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The development of information, technology, and communication has been proven in facilitating the advancement of the digital economy, but it also raises the issue of digital literacy and knowledge about financial technology, especially among Islamic Boarding School’s students. The lack of understanding about financial management and the risks of using financial technology, drive the enhancement on their financial literacy. This community service activity aims to improve financial literacy and utilization of financial technology among students of Al-Ashriyyah Nurul Iman Islamic Boarding School Bogor, West Java. The method that is used in implementing the community service activity is carried out training which is conducted using the classical method and the discussion about digital literacy and the use of financial technology. The results of this activity showed that the level of understanding and ability to utilize financial technology increased significantly. This activity is expected to improve financial literacy among santri and strengthen the integration of digital literacy in the education curriculum